Improving the Vocabulary Mastery of Year Eleven Students Using Mind Mapping Method - Akbar, Muh. Ramadhan; Korompot, Chairil Anwar; Tahir, Muh. (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aims to investigate the effectiveness of the Mind Map Technique in improving vocabulary mastery among Year-Eleven students. This research utilized a mixed-methods approach to explore both qualitative and quantitative data. A pre-experimental design was used, involving 20 students in a single class at SMA Negeri 10 Gowa. The study measured the students' vocabulary mastery before and after receiving treatment through the Mind Map Technique. The results showed that using Mind Maps significantly improved students' vocabulary skills. The pre-test results indicated that only 40% of students achieved an excellent score, while after the treatment, the number of students who earned a perfect score increased to 70%. Moreover, the questionnaire analysis showed that students responded positively to using Mind Maps to improve their vocabulary skills. The findings suggest that the Mind Map Technique can be an effective tool for English teachers to enhance their student's vocabulary skills. Students should be encouraged to use and memorize their vocabulary in real-world situations. This study contributes to the literature on vocabulary instruction and provides a reference for teachers to improve their students' vocabulary mastery using the Mind Map Technique. Future research can explore the potential of Mind Maps to enhance students' skills in other areas, such as writing, listening, and speaking.